Effects of prenatal alcohol exposure on the olfactory system development - Imamura, Fumiaki (Frontiers in Neural Circuits, 2024)
Fetal Alcohol Spectrum Disorders (FASD), resulting from maternal alcohol consumption during pregnancy, are a prominent non-genetic cause of physical disabilities and brain damage in children.Alongside common symptoms like distinct facial features and neurocognitive deficits, sensory anomalies, including olfactory dysfunction, are frequently noted in FASD-afflicted children. However, the precise mechanisms underpinning the olfactory abnormalities induced by prenatal alcohol exposure (PAE) remain elusive. Utilizing rodents as a model organism with varying timing, duration, dosage, and administration routes of alcohol exposure, prior studies have documented impairments in olfactory system development caused by PAE. Many reported a reduction in the olfactory bulb (OB) volume accompanied by reduced OB neuron counts, suggesting the OB is a brain region vulnerable to PAE. In contrast, no significant olfactory system defects were observed in some studies, though subtle alterations might exist. These findings suggest that the timing, duration, and extent of fetal alcohol exposure can yield diverse effects on olfactory system development. To enhance comprehension of PAE-induced olfactory dysfunctions, this review summarizes key findings from previous research on the olfactory systems of offspring prenatally exposed to alcohol.